An improved objective slit-lamp fluorophotometer using tungsten-halogen lamp excitation and synchronous detection. - Smith, A T (1977)
A new design of fluorophotometer is described. The instrument can measure lower concentrations of fluorescent dye with greater accuracy than previous models.